Evidence Based Physiological Adaption Of The Neonate : A Literature review - Sari Rahma Fitri (Cattleya Darmaya Fortuna, 2025)
The birth of a neonate represents one of the most critical transitions in human life, as the new born must rapidly adapt from an intrauterine environment to extrauterine conditions. Within the first minutes and hours after delivery, major physiological adjustments occur in multiple systems, including respiratory, cardiovascular, thermoregulatory, metabolic, and immunological functions. These adaptations are essential to ensure survival and support healthy growth and development. The neonatal period, defined as the first 0–28 days of life, is widely recognized as the most vulnerable stage of childhood, with the highest risk of morbidity and mortality compared to later age groups. Globally, neonatal deaths account for almost half of all deaths among children under five years old, highlighting the urgency of improving neonatal care. Although Indonesia has achieved a gradual reduction in neonatal mortality rates, significant challenges remain in reaching national health targets and ensuring equitable access to quality maternal and new born services. Several conditions continue to contribute substantially to neonatal mortality, including prematurity, birth asphyxia, sepsis, infection, hypo glycemia, intrauterine growth complications, and hypothermia. Inadequate early recognition and delayed management of these problems may lead to severe complications or death. Therefore, healthcare professionals—particularly midwives, nurses, and physicians—must possess comprehensive knowledge of neonatal physiological adaptation in order to provide effective evidence-based interventions during the early postnatal period. This literature review aims to explore the key physiological adaptation processes in neonates and to summarize current evidence-based strategies for early neonatal care. Emphasis is placed on the importance of timely assessment, appropriate clinical management, and supportive interventions to promote a successful transition to extrauterine life. Strengthening neonatal care practices through improved understanding of physiological adaptation is expected to enhance neonatal outcomes, reduce preventable mortality, and contribute to achieving broader maternal and child health goals.